Improving the quality of mental health services in Personal Medical Services pilots: a longitudinal qualitative study. Issue 2 (6th April 2004) - Campbell, S M; Robison, J; Steiner, A; Webb, D; Roland, M O
Abstract : Background: A series of government initatives in the UK have included strategies to improve the quality of services received by patients, including fundholding, the development of National Service Frameworks, clinical governance, and Personal Medical Services (PMS). PMS represents a new contractual arrangement between government and general practitioners (GPs) which provides new investment in return for more detailed specification of processes and outcomes of care. Objectives: To evaluate the effects of PMS on the quality of primary mental health care between 1998 and 2001. Design: Multiple longitudinal case studies. Semi-structured interviews with key staff within practices (GPs, nurses, practice managers) and outside (health authority and primary care group/trust managers). Sample: Six first wave PMS sites which had specifically planned to improve their mental health care. Results: Improvements in mental health care were found in some PMS practices and not in others. Five mechanisms associated with successful quality improvement in mental health were identified: clear goals, effective teamwork within the practice, routine use of protocols and audits, additional resources, and effective collaboration with community and secondary care. Sites where these factors were not present struggled to meet their objectives. Conclusion: The five mechanisms which resulted in improved mental health care were facilitated by the new contractual arrangements in PMS. The new contracts were not a necessary part of these changes, but they enabled sites with an identified interest and motivation to make the changes. The contractual changes were not in themselves sufficient to improve care.